Boosting Tourism in South Coastal Areas: Strategic Marketing for Sustainable Growth - Rizki Alfadillah Nasution; Ghalib Suprianto; Riska Fii Ahsani (Escalate : Economics and Business Journal, 2025)
This research investigates the interrelationships among destination branding, marketing innovation, tourist perception, and tourism growth within the context of tourist attractions in the South Coastal region during the Idul Fitri celebration in 2023. Utilizing a quantitative methodology and a random sampling technique, data were collected from 367 respondents aged 17 to 25 years. The results indicate that destination branding significantly influences both tourism growth and tourist perception, while marketing innovation plays a pivotal role in enhancing destination branding and tourist perception. Notably, although marketing innovation directly impacts tourist perception, its effect on tourism growth is less pronounced. The study underscores the importance of effective branding and innovative marketing strategies in promoting sustainable tourism development, providing valuable insights for stakeholders aiming to enhance destination appeal and drive growth in the tourism sector.